Integration of Team-Based Learning Strategies Into a Cardiovascular Module - Conway, Susan E. (American Journal of Pharmaceutical Education, 2010)
OBJECTIVES: To integrate components of team-based learning (TBL) into a cardiovascular module to increase students' responsibility for their own learning and actively engage students across 2 campuses in patient cases. DESIGN: An existing cardiovascular course module was modified by replacing 8 hours of lectures with self-directed learning (SDL) assignments and transforming case discussion sessions using TBL methodologies. Case discussions were delivered using TBL methods to increase engagement of all students across both campuses while maintaining a low faculty-to-student ratio in the classrooms. Readiness assurance quizzes were performed with each SDL assignment and TBL case session. ASSESSMENT: Student and faculty satisfaction improved with the addition of SDL assignments and TBL cases without adverse effects on grades in the wake of the 14% decrease in lecture time. Total faculty time required increased primarily in the first year because of development of course materials. CONCLUSION: A modified TBL format was successfully integrated into a lecture-based cardiovascular module, resulting in improved student and faculty satisfaction with the course and no adverse effect on student performance.